Pengaruh Penggunaan Smartphone terhadap Perilaku Remaja - Usman Usman; Yulida Maran (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Cell phones have become one of the requirements for the wider community. Today all people in the world can be connected by a modern communication tool that is supported by the development of sophisticated media and modern communication. One of the media such as the mobile phone is now better known as